Business Model Innovation on SMEs: A Literature Review - Desman Hidayat, Christian Haposan Pangaribuan, Okta Prihatma Bayu Putra, Apriani Kurnia Suci (International Journal of Advanced Science and Technology, 2020)
Business model innovation (BMI) has been a popular topic to understand how a company can get its competitive advantages. Despite previous articles on BMI on large companies, the research on business model innovation on small medium enterprises (SMEs) remains limited. This paper gives insights on BMI for SMEs, analyzes the methodology and unit analysis, and provides future directions. The method used for this research is literature review by collecting and analyzing Scopus articles from 2014 until 2020. This paper then conducted a review on the driving factors of BMI, the influence of external factors, as well as the tools and strategic ways for improvement.